Spiritual Level of Intelligence of the Staff of the Ongoing Governmental Departments in the Governorate of Muscat in Light of Some Variables - Amjad M. Hayajneh; Fatma S Al-Ghadani (Sultan Qaboos University, 2014)
This study aimed to detect the levels of availability of the spiritual intelligence of the staff of the government departments in the governorate of Muscat in light of some relevant variables. The study sample consisted of 500 randomly and hierarchically chosen employees: 225 males and 275 females. To achieve the objectives of the study, a proper scale was designed to measure the spiritual intelligence. The results of statistical analysis of the data of the study revealed that the levels of the availability of spiritual intelligence for the members of the sample were high. The arithmetic average for the spiritual intelligence degree for the whole sample was 4.19 from 5, while most of the rest of the 5 dimensions were also high, ranging from 4.19 for the ability to integrate into the virtual behavior to 3.99 for the ability to use spirituality in facing daily problems. The results also showed that non-existence of significant differences in the total averages of IQ spiritual or any of its dimensions among the sample population is attributed to the different variables of gender, age, jobs, and qualifications.